Book Review. Bentz, Valerie Malhotra and Vincenzo M. B. Giorgino, (eds.). 2016. Contemplative Social Research. Caring for Self, Being, and Lifeworld. Santa Barbara: Fielding University Press - Kossakowski, Radosław (Qualitative Sociology Review, 2018)
-